The Perfect Scale for the Depression Diagnosis in the Athletes: A Comparison of the Clinical Tools – Review - Olszanska, Monika; Jurczuk, Aleksandra; Rafałowicz, Adam; Łuniewski, Bartosz; Macko, Angelika; Lauko, Kamil Klaudiusz; Łuniewska, Maria; Nowicka, Iga; Wojciechowska, Urszula Justyna; Marciniak, Kinga (Journal of Education, Health and Sport, 2025)
Background: This review provides a critical analysis of selected clinical assessment instruments for depression, with emphasis on their utility in everyday medical practice and their adaptability to individual patient profiles. Given the multifactorial etiology and diverse symptomatology of depressive disorders, appropriate diagnostic tool selection is essential for accurate evaluation and monitoring. Aim: The paper reviews widely used depression assessment scales, including the Hamilton Depression Rating Scale (HDRS), Montgomery-Åsberg Depression Rating Scale (MADRS), Beck Depression Inventory (BDI), Patient Health Questionnaire (PHQ), Zung Self-Rating Depression Scale (ZSDS), Center for Epidemiologic Studies Depression Scale (CES-D), Depression Anxiety Stress Scales (DASS), and others, analyzing their relevance to various clinical populations, including athletes. Materials and Methods: A structured literature review was conducted using PubMed and Web of Science databases. Keywords included: major depressive disorder, psychometric assessment, screening tools, diagnostic evaluation, and mood disorders. Results: The examined tools differ in structure, scoring methods, and clinical applicability. Their utility varies depending on age, comorbidities, and context. Some instruments are better suited for older adults, postpartum women, or adolescents, while others may offer better sensitivity in athletic populations. Matching the tool to the individual’s clinical and psychosocial profile improves diagnostic accuracy and treatment outcomes. Conclusions: Selecting depression assessment scales based on psychometric quality and population specificity—particularly in underrepresented groups such as athletes—can optimize diagnosis and facilitate effective, personalized treatment strategies.